Managing migrant worker's job satisfaction: A study on a manufacturing company in Malaysia - Thi, Lip Sam; Yong, Kong Hock; Lai, Tian So (2011)
The purpose of this study is to examine and gain a better understanding of the impact of human resource practices on migrant workers' job satisfaction in a manufacturing company. Ninety migrant workers consist of 52 Bangladeshi and 38 Nepalese workers participated in this study. Data was obtained using questionnaires and analyzed. Statistical analysis using regression analysis found the research model has a weak predictive power on migrant workers' job satisfaction. Among the independent variables, only compensation was found to have an impact on migrant workers job satisfaction. T-test results also revealed that Nepalese workers and migrant workers who possess only primary education have higher job satisfaction.